Chapter Advertising Adult Education Offerings in a Portuguese Qualifica Centre using Social Networking Tools - Pereira da Silva, Géraldine (Studies on Adult Learning and Education, 2020)
In the context of adult education, Qualifica Centres throughout Portugal are responsible for the dissemination of adult education pathways available to adult learners. There is a huge variety of dissemination tools. Leaflets, informational notes in the region's newspapers, establishment of partnerships, advertising spots on the radio, and the use of social networks are some of the methods used by centres. This paper on good practices outlines the advertising efforts made by the Qualifica Centre of Azambuja using social networking, specifically the centre's Facebook account, and their results.